Challenges and prerequisites of risk management program in the operating rooms of Iranian hospitals: A qualitative study - Akbar Javan Biparva; Raana Gholamzadeh Nikjoo; Ali Jannati; Mohammad Arab; Ali Ostadi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The World Health Organization (WHO) considers a safe operating room as one of the necessities of hospitals that support patients. Achieving safety in surgical operations in all countries of the world is the basic goal of healthcare centers and organizations; hence, the present study investigated the challenges and prerequisites for the implementation of an active risk management program in the operating rooms of Iranian hospitals. MATERIALS AND METHODS: This qualitative-phenomenological study was conducted in 2022. Data were collected using semi-structured interviews, targeted sampling, and the participation of 20 experts (health policy and management experts and academic officials and faculty members of universities) and executive staff (nurses and operating room technicians, doctors and surgical specialists, and officials of surgical departments) and were analyzed using the framework analysis method. RESULTS: In the resulting qualitative study, the challenges and prerequisites for active risk management in the operating room from the point of view of experts and executive staff were divided into three sub-themes. These three themes include managerial challenges and prerequisites, organizational resources (financial resources, human resources, equipment, and facilities), and cultural issues. CONCLUSION: Considering managerial prerequisites, organizational resources (financial, human, equipment, and facilities), cultural issues, and removing challenges, an active risk management program in the operating room can be implemented correctly. With the correct implementation of this program, injuries in the operating room for personnel and patients will be greatly reduced, and the satisfaction of beneficiaries and the productivity of the hospital will be greatly increased.